2016
DOI: 10.1186/s12933-016-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in cardiovascular structure and function in adolescents with type 1 diabetes

Abstract: BackgroundChildren with type 1 diabetes (T1D) are at higher risk of early adult-onset cardiovascular disease. We assessed cardiovascular structure and function in adolescents with T1D compared with healthy controls and the relationships between peripheral vascular function and myocardial parameters.Methods and results199 T1D [14.4 ± 1.6 years, diabetes duration 6.2 (2.0–12.8) years] and 178 controls (14.4 ± 2.1 years) completed endothelial function by flow mediated vasodilatation (FMD), arterial stiffness usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 64 publications
5
43
1
2
Order By: Relevance
“…The studies were conducted in the United States, Turkey, Canada, Germany, Egypt, Austria, Poland, Estonia, Finland, Greece, Australia, Norway, Mexico, Sweden, Serbia, and the Netherlands between 2002 and 2017. Twenty studies included cIMT as outcome, and four included carotid‐femoral PWV as outcome . The characteristics of all 23 studies used for the systematic review are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in the United States, Turkey, Canada, Germany, Egypt, Austria, Poland, Estonia, Finland, Greece, Australia, Norway, Mexico, Sweden, Serbia, and the Netherlands between 2002 and 2017. Twenty studies included cIMT as outcome, and four included carotid‐femoral PWV as outcome . The characteristics of all 23 studies used for the systematic review are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although this study could not show significantly different diastolic parameters at rest, diabetic children might have impaired diastolic functional reserve during exercise 7). Recently, two-dimensional speckle tracking echocardiographic studies to demonstrate LV mechanical dysfunction more sensitively and a few studies have published in children with type 1 DM 8)9). Hensel et al10) reported that asymptomatic type 1 DM children had signs of hyperdynamic LV contractility early in the course of the disease.…”
mentioning
confidence: 73%
“…Полинейропатия, n (%) / Neuropathy, n (%) 27 (38) Ангиопатия, n (%)/ Angiopathia, n (%) 17 (23,9) Ретинопатия, n (%) / Retinopathy, n (%) 1 (1,4)…”
Section: результаты и обсуждениеunclassified
“…Патологические изменения со стороны сердечной мышцы, возникающие при СД, расцениваются как диабетическая кардиомиопатия (КМП) [2,19,23,24].…”
Section: Introductionunclassified